Quiet resonances of an emergent indigeneity: sound, silence, and igorot protest performances in the Philippines - Decenteceo, Lisa (Tanjong Malim, 2024)
Quiet resonances of an emergent indigeneity: sound, silence, and igorot protest performances in the Philippines by Decenteceo, Lisa